Republic of Poland : Technical Assistance Report-Macroprudential Framework. (IMF Staff Country Reports; Country Report ;, 2012)
This paper on the Republic of Poland was prepared by a staff team of the International Monetary Fund as background documentation for the periodic consultation with the member country. It is based on the information available at the time it was completed in July 2012. The views expressed in this document are those of the staff team and do not necessarily reflect the views of the government of the Republic of Poland or the Executive Board of the IMF.